NO3− anions can act as Lewis acid in the solid state - Antonio Bauzá (Nature Portfolio, 2017)
The nitrate anion, NO3−, is typically thought of as an electron-donating molecular moiety. Here the authors reveal, however, that when the negative charge on NO3−is smeared out over a large enough area, a positive potential emerges on N that can act as a Lewis acid in the solid state.